(untitled) (Academicia Globe: Inderscience Research, 2021)
This article is based on the development of proposals and recommendations related to the formation of spiritual and moral education of students through the scientific heritage of hadith scholars. The useful aspects of hadiths in the upbringing of young people in the "Education" classes of 5-7 grades are also revealed.